Green Synthesis of Nanomaterials and Their Biological Applications - Benelli, Giovanni (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The book "Green Synthesis of Nanomaterials and Their Biological Applications" present novel advances about the green synthesis of nanomaterials, as well as on the possible biological applications, including studies dealing with entomology, parasitology, biomedicine, and environmental research.